2022
DOI: 10.1261/rna.079475.122
|View full text |Cite
|
Sign up to set email alerts
|

Human RNase P: overview of a ribonuclease of interrelated molecular networks and gene-targeting systems

Abstract: The seminal discovery of ribonuclease P (RNase P) and its catalytic RNA by Sidney Altman has not only revolutionized our understanding of life, but also opened new fields for scientific exploration and investigation. This review focuses on human RNase P and its use as a gene targeting tool, two topics initiated in Altman’s laboratory. We outline early works on human RNase P as a tRNA processing enzyme and comment on its expanding non-conventional functions in molecular networks of transcription, chromatin remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…RNAse P is found both in the cytoplasm and mitochondria and functions in maturation of tRNA molecules. 6,7 Both ribonucleoproteins are evolutionary and structurally related. POP1, is one of 11 interacting proteins of these complexes, composed of a short N-terminal domain, internal motif and a large C-terminal motif.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RNAse P is found both in the cytoplasm and mitochondria and functions in maturation of tRNA molecules. 6,7 Both ribonucleoproteins are evolutionary and structurally related. POP1, is one of 11 interacting proteins of these complexes, composed of a short N-terminal domain, internal motif and a large C-terminal motif.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing in the POP1 gene results in multiple transcript variants with no tissue specifity. [6][7][8] Previous studies have shown that mutations in POP1, lead to RMRP depletion, suggesting that alterations in ribosomal biogenesis are a major pathogenic mechanism for severe short stature and skeletal dysplasia. 9,10 Our patient's RMRP level is lower than in reported cases, the same holds for the increase in Pre-5.8S.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this, the M1GS ribozyme can be used to target both cytoplasmic and nuclear mRNAs while the EGS-mediated gene targeting action to downregulate gene expression is believed to work in the nuclei where human RNase P is primarily localized [ 38 ]. Moreover, the M1GS ribozyme is different from human RNase P, which contains at least 10 different protein subunits and a RNA subunit (H1 RNA), which is hardly catalytically active in the absence of the protein subunits [ 3 , 40 ].…”
Section: Discussionmentioning
confidence: 99%